Diet and Non-Alcoholic Fatty Liver Disease (NAFLD): Advances and Management Strtegies : A Comprehensive Review - S, Syeda Farha; R, Sheetal (Universitas Airlangga, 2025)
Global public health is at risk from non-alcoholic fatty liver disease, or NAFLD. Fat accumulation in the liver is associated with chronic liver disease (NAFLD), even in the absence of significant alcohol consumption. It could have anything to do with liver inflammation and fibrosis. Because non-communicable diseases have become more common over the past few years, changing one’s lifestyle has drastically altered the priorities for health. Between 1990 and 2017, the number of people worldwide with NAFLD grew from 19.34 million to 29.49 million. An estimated 35.4% of Indians are believed to have NAFLD. Nonalcoholic fatty liver disease is the term used when there is no alcohol intake, and ectopic fat deposition exceeds 5% of the weight of the liver (NAFLD). It encompasses a broad range of morphologically diverse liver abnormalities, from basic steatosis to severe forms like non-alcoholic steatohepatitis (NASH), a progressive form of the disease marked by fibrosis, hepatocyte ballooning degeneration, and lobule inflammation. Obesity, diabetes, dyslipidemia, and the so-called insulin resistance or metabolic syndrome are linked to primary NAFLD/NASH. Rarely, secondary NAFLD/NASH can be linked to a variety of illnesses, including pancreatic duodenal resection, endocrine disorders, polycystic ovary syndrome, and sleep apnea. Today's kids face an unparalleled dietary challenge. Food is abundant, yet a growing proportion of kids are overweight or obese due to inadequate nutrition. Hyperinsulinemia with insulin resistance seems to be crucial in pediatric NAFLD. Understanding pediatric NAFLD's pathophysiology is anticipated to enhance our understanding of the condition. Additionally, finding prevention treatments for pediatric NAFLD is imperative for the well-being of children.